Efficient photocatalytic hydrogen evolution with ligand engineered all-inorganic InP and InP/ZnS colloidal quantum dots - Shan Yu (Nature Portfolio, 2018)
While quantum dots show high efficiency solar-to-fuel conversion for renewable energy, the frequently toxic elements employed present severe safety concerns. Here, authors demonstrate indium phosphide quantum dots as low-toxicity alternatives alongside efficient hydrogen evolution photocatalysis.